Radical addition approach to asymmetric amine synthesis: Design, implementation, and comparison of chiral N-acylhydrazones - Friestad, GK; Draghici, C; Soukri, M; Qin, J (Journal of organic chemistry, 2005)
Intermolecular radical addition to C=N bonds with acyclic stereocontrol offers excellent potential as a mild, nonbasic carbon-carbon bond construction approach to chiral amines. Here, complete details of the first radical additions to chiral N-acylhydrazones as an approach to asymmetric amine synthesis are disclosed. Novel N-acylhydrazones were designed as chiral C=N radical acceptors with Lewis acid activation, restriction of conformational mobility, and commercial availability of precursors. Amination of 4-alkyl-2-oxazolidinones with O-(mesitylenesulfonyl)hydroxylamine or O-(pnitrobenzoyl)hydroxylamine afforded N-aminooxazolidinones which were condensed with aldehydes to afford N-acylhydrazones 3-8. Three synthetic methods were developed, implementing these N-acylhydrazones in Lewis acid-promoted intermolecular radical additions to C=N bonds. First, additions of various secondary and tertiary alkyl iodides to propionaldehyde and benzaldehyde hydrazones (3 and 7) under tin hydride radical chain conditions in the presence of ZnCl2 gave N-acylhydrazine adducts with diastereomeric ratios ranging from 93:7 to 99:1. Radical additions to a series of N-acylhydrazones with different substituents on the oxazolidinone revealed that benzyl and diphenylmethyl were more effective stereocontrol elements than those with the aromatic ring directly attached to the oxazolidinone. Second, a tin-free method, exploiting dual functions of triethylborane for both initiation and chain propagation, enabled improved yields in addition of secondary alkyl iodides. Third, under photolytic conditions with hexamethylditin, primary radical addition could be achieved with ethyl iodide in the presence of diethyl ether as cosolvent; the 1-ethoxyethyl adduct was observed as a minor product. Chloromethyl addition was achieved under both the tin-free and photolytic conditions; in this case, the adduct bears alkyl chloride functionality with potential for further elaboration.